2009
DOI: 10.2134/jeq2008.0365
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Lincomycin to Surface and Ground Water from Manure‐amended Cropland

Abstract: Livestock manure containing antimicrobials becomes a possible source of these compounds to surface and ground waters when applied to cropland as a nutrient source. The potential for transport of the veterinary antimicrobial lincomycin to surface waters via surface runoff and to leach to ground water was assessed by monitoring manure-amended soil, simulated rainfall runoff, snowmelt runoff, and ground water over a 2-yr period in Saskatchewan, Canada, after fall application of liquid swine manure to cropland. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 38 publications
5
25
1
2
Order By: Relevance
“…Concentrations of lincomycin in the A-w sample and B-w, C-w, D-w, E-w samples detected in this study were similar to previous studies of liquid swine manure and ground water from manure-amended cropland, respectively (Kuchta and Cessna, 2009a; Kuchta et al, 2009). However, lincomycin residues in soil samples were higher than that in manure-amended soil reported previously (Kuchta et al, 2009). Lincomycin residues declined substantially downstream of site A probably as a result of dilution.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concentrations of lincomycin in the A-w sample and B-w, C-w, D-w, E-w samples detected in this study were similar to previous studies of liquid swine manure and ground water from manure-amended cropland, respectively (Kuchta and Cessna, 2009a; Kuchta et al, 2009). However, lincomycin residues in soil samples were higher than that in manure-amended soil reported previously (Kuchta et al, 2009). Lincomycin residues declined substantially downstream of site A probably as a result of dilution.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies indicated that antibiotic residues in the environment (soil and water) could affect the selection and dissemination of resistance genes, and promote or inhibit ecological functions (Ghosh and Lapara, 2007; Naslund et al, 2008; Schauss et al, 2009; Ding and He, 2010). Therefore, long-term use of lincomycin, coupled with its slow degradation in soil and water (Kuchta et al, 2009; Williams and McLain, 2012) could potentially lead to the selection of resistant bacteria species and the transfer of ARGs located in transferable elements (Looft et al, 2012). This hypothesis will be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, antimicrobials used in veterinary medicine are administered to livestock at therapeutic levels to treat disease and at subtherapeutic levels to increase weight gain through increased feed efficiency (Sarmah, Meyer, & Boxall, ). As a result, antimicrobials have been shown to be present in beef cattle (Cessna et al., ; Sura et al., ), poultry (Karci & Balcioǧlu, ; Martínez‐Carballo, González‐Barreiro, Scharf, & Gans, ), and swine (Kuchta, Cessna, Elliott, Peru, & Headley, ; Martínez‐Carballo et al., ) manure.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, application of raw or processed (composted or stockpiled) manure to fertilize agricultural land is a major route by which antimicrobials enter the broader environment. Subsequent transport of antimicrobials in snowmelt or rainfall runoff from manure‐amended crop (Amarakoon et al., ; Dolliver & Gupta, ; Hoese et al., ; Kuchta et al., ) or grass land (Burkhardt, Stamm, Waul, Singer, & Müller, ; Kuchta & Cessna, ; Stoob, Singer, Mueller, Schwarzenbach, & Stamm, ), and from feedlots (Sura et al., ) and manure composting and stockpiling facilities (Dolliver & Gupta, ; Sura et al., ) can lead to their presence in surface receiving waters.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Dolliver et al (2008) reported that antibiotic degradation was similar whether manure was stockpiled, composted by active mixing or composted in-vessel. The slow degradation of antibiotics in manure at low temperatures (Arikan et al 2009a, b) could be a concern in the northern USA and Canada where livestock manure is often applied in late fall, raising the possibility that antibiotics could persist in manured soil for a considerable period of time (Kuchta et al 2009). …”
mentioning
confidence: 99%